Important issues of professional burnout among hematologists and hematology department nursing staff during the COVID-19 pandemic - O. A. Aleshina; T. P. Nikitina; N. M. Porfirieva; D. E. Vybornykh; E. N. Parovichnikova; T. I. Ionova (Онкогематология)
Background. Professional burnout (PB) among medical staff, namely hematologists, is of major importance, especially given the current shortage of personnel. It is of extreme value during the COVID-19 pandemic.Aim. To determine the degree of PB development among hematologists and nursing staff of hematological departments of federal and regional medical institutions in the context of the COVID-19 pandemic and to identify the associated factors.Materials and methods. The study was conducted in the period from July 2022 to September 2022 in the form of a onetime online survey of hematologists and nursing staff of hematology departments of federal and regional medical institutions in different cities of the Russian Federation. To interview specialists, a special checklist based on an Internet resource (Google forms) was used. It included burnout questionnaire Maslach Burnout Inventory (MBI) and questions related to factors that may be associated with the formation of PB. Statistical analysis included pairwise and multiple comparisons, as well as χ2 test, correlation and logistic regression analysis.Results. A total of 162 specialists took part in the online survey. More than half of the specialists (52 %) had high degree of emotional exhaustion, high level of depersonalization was detected in 39.5 % of specialists, and low level of personal accomplishment – in one third of specialists (32.1 %). It was shown that physicians, compared with nurses, had significantly higher indicators of PB. The level of problems for all PB components was significantly lower among specialists working in federal health facilities than among specialists working in regional clinics. The specialists who worked in the “red zone” showed a greater degree of emotional exhaustion and depersonalization than the specialists who did not work in the “red zone” during the pandemic. The formed PB syndrome was observed in 16 % of specialists, and its signs – in 42 %. The risk of PB was significantly greater in hematologists than in nurses, as well as among specialists with increased levels of depression and anxiety and dissatisfaction with the level of personal protective measures.Conclusion. The high importance of PB and the need for preventive measures among specialists of hematological centers and hematology departments in the Russian Federation is shown.